The way we perceive a place implies who can live there: Essentialisation of place and attitudes towards diversity. (June 2021) - Wnuk, Anna; Oleksy, Tomasz; Toruńczyk-Ruiz, Sabina; Lewicka, Maria
Abstract: In the contemporary world of human mobility, one of the key problems is why different groups of people are welcomed in some places, but are driven away from others. Theoretical writings of geographers, sociologists, and architects suggest that place can be defined in two ways—as an essentialist, bounded entity with historical continuity or as an open, anti-essentialist space, supporting changes. We hypothesized that in the minds of lay people, these two types of places allow for either a small or high level of ethnic diversity, and thus a certain view of a place would have consequences for acceptance of outgroup members in that place. In three online experimental studies participants were asked to think of a real or imagined place focusing on its specific features, which were either essentialist or anti-essentialist. A consistent pattern of findings showed that conceiving of a place as anti-essentialist was related to greater openness towards the presence of ethnic outgroup members in that place compared to perceiving it as essentialist. Our study contributes to understanding which features of a particular place may foster its perception as more open and inclusive and, conversely, which features are related to a representation of the place as closed and unfriendly to certain ethnic groups. Highlights: Places differ in whether they are perceived as essentialist or anti-essentialist. How people perceive a place affects attitudes towards ethnic diversity in that place. Viewing a place as anti-essentialist leads to higher endorsement of ethnic diversity.